2022
DOI: 10.1590/1519-6984.241162
|View full text |Cite
|
Sign up to set email alerts
|

First case of canine visceral leishmaniasis in the midwestern of Santa Catarina State, Brazil

Abstract: Canine visceral leishmaniasis (CVL) caused by Leishmania (Leishmania) infantum is transmitted by phlebotomine sandflies and a major zoonotic disease in Brazil. Due to the southward expansion of the disease within the country and the central role of dogs as urban reservoirs of the parasite, we have investigated the occurrence of CVL in two municipalities Erval Velho and Herval d’Oeste in the Midwest region of Santa Catarina state. Peripheral blood samples from 126 dogs were collected in both cities and tested f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Several studies in other Brazilian cities have described autochthonous cases of CL (Tolezano et al, 2007;Silva et al, 2011;Faria et al, 2017, Silva et al, 2018Rocha et al, 2018, Pinto et al, 2021. Furthermore, although animals from Belém have been diagnosed with leishmaniasis (antibody detection) in two other studies (Campos et al, 2017, Schwanke et al, 2014 neither study indicated that the animals were born in Belém and never lived or traveled to endemic areas, as described for the animals in this study.…”
Section: Discussionmentioning
confidence: 45%
“…Several studies in other Brazilian cities have described autochthonous cases of CL (Tolezano et al, 2007;Silva et al, 2011;Faria et al, 2017, Silva et al, 2018Rocha et al, 2018, Pinto et al, 2021. Furthermore, although animals from Belém have been diagnosed with leishmaniasis (antibody detection) in two other studies (Campos et al, 2017, Schwanke et al, 2014 neither study indicated that the animals were born in Belém and never lived or traveled to endemic areas, as described for the animals in this study.…”
Section: Discussionmentioning
confidence: 45%
“…However, in the Metropolitan Region of São Paulo (RMSP), state of São Paulo, CVL occurs in rural areas close to forest fragments, which provides access for dogs to these fragments, in addition to socializing with other animals around the house, such as cats, swine, equine and chickens. In the state of Santa Catarina, Pinto et al (2022) found the same situation in relation to dogs with CVL, that is, the presence and possible and possible entry into forest areas, in addition to the occurrence of poultry and swine farms in the vicinity of the houses. In the RMSP, sand fly collections were carried out in places where cases of CVL occurred, however, the L. longipalpis vector was only detected in the municipality of Caieiras ( Pimont et al, 2015 ).…”
mentioning
confidence: 69%
“…The first CanL autochthonous case was reported in São Borja, a city bordering the province of Corrientes, Argentina, in 2008 [4]. Other studies detected CanL in geographical regions of Argentina bordering Brazil as well as in cities from the Brazilian southernmost states (Rio Grande do Sul and Santa Catarina) a few years later [5][6][7][8]. The recent widespread dispersion of Lu.…”
Section: Introductionmentioning
confidence: 99%